Alcohol disrupts the effects of priming on the perception of ambiguous figures. (January 2014) - O'Brien, Claire; Higgs, Suzanne; Harris, Mike
Inhibitory mechanisms are thought to underpin the well-documented impairing effects of alcohol on attention. Here, we use a novel priming paradigm to investigate the effects of alcohol on inhibitory mechanisms in attention. Participants were assigned to an alcohol ( N =15), or placebo ( N =15) group. The dose of alcohol was 0.8 g/kg for males and 0.75 g/kg for females. Participants were asked to report figure reversals during presentation of the face–vase ambiguous figure. Prior to this, they were shown a prime that was either semantically relevant to the face–vase stimulus or was neutral. Semantic priming decreased the number of figure reversals in the first half of the test session in the placebo group but not in the alcohol group. The placebo group was also more likely than the alcohol group to report the first interpretation of the figure to be the same as the semantic prime. Prior presentation of a semantic prime had a stabilising effect on reversal rate, suggesting that the primed interpretation inhibited the alternate interpretation. The absence of an effect in the alcohol group is consistent with an alcohol-related impairment of this inhibition.